Peran Event MICE sebagai Media Promosi Sektor Ekonomi Kreatif dan UMKM di Kota Medan - Eni Kusuma Amalia Ningrum (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
ABSTRAK This study aims to analyze (1) the role of MICE events as a promotional medium for the creative economy and MSME sectors in Medan City, (2) strategies to enhance that role, and (3) factors influencing its optimization. The research employs a qualitative approach with purposive sampling of key stakeholders in the MICE ecosystem, creative economy actors, and MSME owners, using in-depth interviews, event observations conducted from August to October 2025, and document analysis, which are validated through source and method triangulation. The findings indicate that MICE events have functioned as an effective promotional medium for creative economy actors and MSMEs, while the enhancement strategy is formulated as an integration flow of MSMEs into the MICE supply chain, covering pre-event, during-event (strategic placement and promotional activation), and post-event phases. The optimization of this role is strongly influenced by three main factors: the absence of clear technical regulations, limited competencies and institutional capacity of MSMEs/creative economy actors, and event infrastructure design and management that do not yet fully favor local players. Overall, the study concludes that MICE events in Medan City hold significant potential as a promotional medium for the creative economy and MSME sectors but require policy reinforcement, capacity building for local actors, and improvements in event design and management to function optimally as a lever for competitiveness and sustainability of local businesses.